Single-centre, triple-blinded, randomised, 1-year, parallel-group, superiority study to compare the effects of Roux-en-Y gastric bypass and sleeve gastrectomy on remission of type 2 diabetes and β-cell function in subjects with morbid obesity: a protocol for the Obesity surgery in Tønsberg (Oseberg) study. Issue 6 (4th June 2019) - Borgeraas, Heidi; Hjelmesæth, Jøran; Birkeland, Kåre Inge; Fatima, Farhat; Grimnes, John Olav; Gulseth, Hanne L; Halvorsen, Erling; Hertel, Jens Kristoffer; Hillestad, Tor Olav Widerøe; Johnson, Line Kristin; Karlsen, Tor-Ivar; Kolotkin, Ronette L; et al.
Abstract : Introduction: Bariatric surgery is increasingly recognised as an effective treatment option for subjects with type 2 diabetes and obesity; however, there is no conclusive evidence on the superiority of Roux-en-Y gastric bypass or sleeve gastrectomy. The Oseberg study was designed to compare the effects of gastric bypass and sleeve gastrectomy on remission of type 2 diabetes and β-cell function. Methods and analysis: Single-centre, randomised, triple-blinded, two-armed superiority trial carried out at the Morbid Obesity Centre at Vestfold Hospital Trust in Norway. Eligible patients with type 2 diabetes and obesity were randomly allocated in a 1:1 ratio to either gastric bypass or sleeve gastrectomy. The primary outcome measures are (1) the proportion of participants with complete remission of type 2 diabetes (HbA1c≤6.0% in the absence of blood glucose-lowering pharmacologic therapy) and (2) β-cell function expressed by the disposition index (calculated using the frequently sampled intravenous glucose tolerance test with minimal model analysis) 1 year after surgery. Ethics and dissemination: The protocol of the current study was reviewed and approved by the regional ethics committee on 12 September 2012 (ref: 2012/1427/REK sør-øst B). The results will be disseminated to academic and health professional audiences and the public via publications in international peer-reviewed journals and conferences. Participants will receive a summary of the main findings. Trial registration number: NCT01778738 ;Pre-results.